Impact of salt reduction on biogenic amines, fatty acids, microbiota, texure and sensory profile in traditional blood dry-cured sausages - Laranjo, Marta; Gomes, Ana; Agulheiro-Santos, A.C.; Potes, M.E.; Cabrita, Maria João; Garcia, Raquel; Rocha, João Miguel; Roseiro, Luisa Cristina; Fernandes, Maria José; Fraqueza, Maria João; Elias, Miguel (My University, 2017)
Meat industry needs to reduce salt in their products due to healthy issues. The present study evaluated the effect of salt reduction from 6% to 3% in two Portuguese traditional blood dry-cured sausages. Physico-chemical and microbiological parameters, biogenic amines, fatty acids and texture profiles and sensory panel evaluations were considered. Differences to salt reduction were preceptible in a faint decline of water activity, which slightly favoured microbial growth. Total biogenic amines content ranged from 88.86 to 796.68 mg Kg-1 fresh matter, with higher amount, particularly of cadaverine, histamine and tyramine, in low-salt products. Still, histamine anda other vasoactive amines remained at low levels, thus not affecting consumers' health. Regarding fatty acids, no significant differences were observed due to salt. However, texture profile analysis revealed lower resilience and cohesiveness in low-salt products, although no textural changes were observed by the sensory panel. Nevertheless, low-salt sausages were clearly preferred by panellists.
Keywords: dry-cured sausages; blood; biogenic amines; fatty acids; microbiology; food safety; texture profile analysis; sensory evaluation